Ergonomi- och designutveckling av arbetsväska för kassörer på nöjespark - Andersson, Sofie; Kayedan, Tina (My University, 2024)
Liseberg is an amusement park with many different functions and departments. The department of “Park Service” is responsible for the sale of products in the park. The workers in this department use a work bag to carry the products from and to their position for about ten minutes.This project investigates and evaluates the needs and requirements for the cashiers regarding their work bag. The basis of the project was laid by researching, observing, and interviewing relevant parties. By leveraging different design principles, the results from the user study provided a clear foundation for the next phase; idea generation and product development. Various factors such as safety, ergonomics, and user friendliness needed to be taken into account while brainstorming and designing possible concepts. By conducting different evaluation methods, an optimized concept could be generated. To guarantee that the best concept had been chosen, the users were brought back in to try and verify the quality and theory of the new concept. This way the credibility of the project became higher, while giving the users a second chance to give feedback and suggest possible improvements. The concept was then adjusted according to the users feedback and other problems that had occured. At last, a well thought-out design could be presented, backed up with reasonable arguments and facts behind every design decision.
Keywords: Product development; Ergonomic; User research; Product design